A compact 0.5 T MR elastography device and its application for studying viscoelasticity changes in biological tissues during progressive formalin fixation - Braun, Juergen; Tzschaetzsch, Heiko; Koerting, Clara; De Schellenberger, Angela Ariza; Jenderka, Marika; Driessle, Toni; Ledwig, Michael; Sack, Ingolf (Magnetic Resonance in Medicine, 2018)
Purpose: To develop a method of compact tabletop magnetic resonance elastography (MRE) for rheological tests of tissue samples and to measure changes in viscoelastic powerlaw constants of liver and brain tissue during progressive fixation. Methods: A 10-mm bore, 0.5-T permanent-magnet–based MRI system was equipped with a gradient-amplifier–controlled piezo-actuator and motion-sensitive spin echo sequence for inducing and measuring harmonic shear vibrations in cylindrical samples. Shear modulus dispersion functions were acquired at 200–5700 Hz in animal tissues at different states of formalin fixation and fitted by the springpot powerlaw model to obtain shear modulus μ and powerlaw exponent α. Results: In a frequency range of 300–1500 Hz, unfixed liver tissue was softer and less dispersive than brain tissue with μ = 1.68 ± 0.17 kPa and α = 0.51 ± 0.06 versus μ = 2.60 ± 0.68 kPa and α = 0.68 ± 0.03. Twenty-eight hours of formalin fixation yielded a 400-fold increase in liver μ, 25-fold increase in brain μ, and two-fold reduction in α of both tissues. Conclusion: Compact 0.5-T MRE facilitates automated measurement of shear modulus dispersion in biological tissue at low costs. Formalin fixation changes the viscoelastic properties of tissues from viscous-soft to elastic-stiff more markedly in liver than brain. Magn Reson Med 79:470–478, 2018. © 2017 International Society for Magnetic Resonance in Medicine.
CRIS-Team Scopus Importer:2022-08-03
Keywords: brain; cylinder geometry; liver; magnetic resonance elastography; powerlaw; soft tissue rheology; springpot; vibrations